Environmental policy and exports: Evidence from China - Sandra Poncet; Laura Hering (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
This paper assesses the effectiveness of environmental regulations in China. Our identication is based on the environmental policy of the Two Control Zones (TCZ), which was implemented by the Chinese government in 1998. The aim of this policy was to reduce sulfur dioxide (SO2) emissions in targeted cities with particularly severe air pollution. We use export data from 265 Chinese cities among which 158 were targeted by this policy, and exploit variations over time, sector and firm type to establish the causal effect of this policy on exports. Our results are robust to using an instrumental variable approach. Tougher environmental regulations lead to the reallocation of export activities away from energy-intensive sectors. In line with a suspicion of differences in policy enforcement according to the political pecking order of firms, the TCZ policy is found to have a greater impact the lower the firm's political status.
Keywords: F10; F18; Q53; Q56; 330